A facile synthesis of monodispersed hierarchical layered double hydroxide on silica spheres for efficient removal of pharmaceuticals from water - Chen, Chunping (2013)
Monodispersed layered double hydroxide (LDH) spheres with a hierarchical structure have been synthesized via a facile ultrasound-assisted method. The as-obtained 3D LDH spheres present excellent and durable performance for the removal of pharmaceutical pollutants from aqueous solutions.